DEMENTIA FRIENDLY HOSPITALS FROM A UNIVERSAL DESIGN APPROACH: RESEARCH AND GUIDELINES. (16th November 2018) - Grey, T; Xidous, D; Kennelly, S; Timmons, S; O'Neill, D
Abstract: Background: For many patients, the hospital is challenging due to the busy, unfamiliar, and stressful nature of the environment. For a person with dementia this experience can be exacerbated by cognitive impairment and behavioural or psychological symptoms. Research was conducted into how the built environment in acute hospitals could be more supportive for patients with dementia and their families. The research was underpinned by Universal Design to ensure that the resulting guidelines supported the wide spectrum of ages, abilities and disabilities represented in the typical hospital. The paper presents the key research findings and outlines the resulting guidelines. Methods: The project involved a literature review, stakeholder engagement, international desk-based case studies, and detailed onsite analysis in three hospital settings. Finally, a transdisciplinary steering committee oversaw the project and approved the resulting guidelines. Results: The research findings were organised into themes and grouped into three areas: underlying issues; design issues across spatial scales; and, barriers and facilitators, and used to underpin, structure, and provide content for the new guidelines. Conclusion: This research confirms the negative impact of the hospital setting on many patients with dementia. It identified the wide variety of needs and preferences within hospitals, while also stressing the important supporting role played by an accompanying person, not only for patients, but also for staff. The research highlighted the need to consider the hospital across the full spatial spectrum, from approaching and entering the campus, internal circulation, and down to more detailed aspects such as building components and technology.